Species Investigation of Rice Stem Borers and Its Parasitoids on Fallowing Rice Fields at Karawang, Indonesia - Anwar, Ruly; Sartiami, Dewi; Rauf, Aunu (AGRIVITA Journal of Agricultural Science, 2024)
Rice stem borers (RSB) cause the same damage symptoms and occur through the season and time. During the off-season for rice, these stem borers are not well-known. The research aims to determine the effect of fallowing rice on the presence of rice stem borers and their parasitoids, the potential for RSB infestation, and their parasitoid on subsequent rice seedlings in nurseries at Karawang Regency, West Java. Several variables are observed, including the number of rice stem borer larvae on stubbles, egg masses, the percentage of parasitized eggs, and the number of adults of rice stem borer in nurseries. The results show that species of rice stem borer on the fallow rice are Scirpophaga incertulas and Sesamia inferens. The population of S. incertulas is significantly higher on long rice fallow. The height of the paddy stubble at the two locations is not very different. However, the infested stubble in the short fallow period is higher than those in the long fallow. Eggs of S. incertulas whose high percentage hatched and parasitized, are primarily found in nurseries of areas with long fallow. There are three species of parasitoids identified.